Statin Prescription Patterns Among Elderly Patients with Type 2 Diabetes: A Cross-Sectional Study in Lebanon - Farah Al Souheil; Bahia Chahine (Adis, Springer Healthcare, 2022)
Abstract Background Even though statins have been proven to be effective in both primary and secondary prevention of cardiovascular disease among diabetic patients, a suboptimal use of the latter has been detected in real clinical practice, especially among older adults. Objective This study aimed to evaluate the patterns and predictors of statin use among elderly patients with type 2 diabetes mellitus (T2DM) in Lebanon. Methods This is a cross-sectional study that extended between April 2021 and February 2022. Our study involved elderly T2DM outpatients, aged 65-80 years, who presented to 40 community pharmacies for prescription filling. Diabetes status was ascertained via dispensed medication information, and patients were classified based on the American Diabetes Association preset risk scores for cardiovascular diseases in diabetics: low, moderate, or high risk. The questionnaire included patients' demographics, clinical information, and status of statin use. Results A total of 420 diabetic geriatric patients were observed in this study; their mean age was 70 years (± 7), and there was a predominance of males, 270 (64.3%). Almost all patients were classified as being at high risk, 396 (94.3%), while the rest were at moderate risk; thus, all were recommended to receive statins; however, statin prescription was only reported among 197 (46.9%), with atorvastatin and rosuvastatin being the most used: 102 (51.8%) and 62 (31.5%), respectively. Of patients prescribed statins, 60 (14.3%) were taking them for primary prevention and 137 (32.6%) for secondary prevention. Patients having a higher Charlson Comorbidity Index score had lesser odds of being prescribed statins (odds ratio [OR] 0.15, 95% confidence interval [CI] 0.02-0.8, p = 0.028); however, those presenting with a history of dyslipidemia and coronary artery disease had higher odds of statin prescription (OR 10.5, 95% CI 4.2-26.1, p < 0.001, and OR 5.0, 95% CI 2.4-10.5, p < 0.001, respectively). Conclusion Despite patients' eligibility to receive statins, statin undertreatment was evident among elderly outpatients with T2DM in Lebanon, which was modulated by several predictors.